Trends in water borne diseases in Kerala: an analysis of directorate of health services portal data - V., Soorya; Raj, Jishnu; K. R., Anitha Kumari (International Journal of Research in Medical Sciences, 2021)
Background: Kerala faces high mortality-morbidity rates from water borne diseases. For the timely management of communicable diseases, understanding trends, pattern and seasonality of disease was important. The aim was to find out the trend, pattern and seasonal variation of water borne diseases in Kerala. Methods: Retrospective record based descriptive study was done to find out the trend and pattern of water borne diseases and to find out its seasonal variation in Kerala. Data from the DHS (directorate of health services) portal during 2011 to 2019 were collected and analyzed. Results: More than 97 percent of water borne diseases are due to diarrheal diseases but no death reported. A rising trend in diarrheal disease is observed. Typhoid, hepatitis A and cholera showed decreasing trend. Leptospirosis shared only 0.2 to 0.4 percent, but death rate was high. Malapuram tends to report most number of cases but percentage share was highest from Kozhikode in 2011. Palakkad reported highest number and Kottayam lowest among central districts. Among southern districts, Thiruvananthapuram reported highest number of cases and Pathanamthitta lowest. Malappuram showed declining trend among northern districts while least number of cases were reported from Wayand district. Seasonal variability was observed in 2011-2013 and 2018. Conclusions: Seasonal variation in occurrence of water borne diseases in rainy season is statistically significant when compared to winter season. Data on water borne disease other than diarrheal diseases is a matter of concern.